2007
DOI: 10.1108/09600030710825676
|View full text |Cite
|
Sign up to set email alerts
|

Postponement: an evolving supply chain concept

Abstract: Purpose -The purpose of this paper is to assess and document the progress of postponement research, identify current gaps, and provide direction for future research efforts. Design/methodology/approach -Postponement literature published from 1999 to 2006 was reviewed. Findings -The review revealed a significant increase in the number of postponement research efforts, many of which at least partially addressed past challenges noted in previous research. Several opportunities to continue addressing these past ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
78
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 45 publications
0
78
0
2
Order By: Relevance
“…In addition, SCR can increase from contextual issues, including updating contracting mechanisms to focus on performance (Berkowitz et al, 2005), developing logistics capabilities (Gligor and Holcomb, 2012), using third party logistics providers (Min, 2013), locating DCs in disasters (Yushimito et al, 2012), emergency logistics (Hu and Zhao, 2011) and humanitarian logistics (Kovács and Spens, 2012), evolving military and commercial logistics practices (Rutner et al, 2012), and postponement as applied to inventory management (Boone et al, 2007), mass customisation (Kim, 2014), assembly (van Hoek et al, 1998), packaging (Seth and Panigrahi, 2015), and information logistics (Dinter, 2013).…”
Section: Logistics and Distributionmentioning
confidence: 99%
“…In addition, SCR can increase from contextual issues, including updating contracting mechanisms to focus on performance (Berkowitz et al, 2005), developing logistics capabilities (Gligor and Holcomb, 2012), using third party logistics providers (Min, 2013), locating DCs in disasters (Yushimito et al, 2012), emergency logistics (Hu and Zhao, 2011) and humanitarian logistics (Kovács and Spens, 2012), evolving military and commercial logistics practices (Rutner et al, 2012), and postponement as applied to inventory management (Boone et al, 2007), mass customisation (Kim, 2014), assembly (van Hoek et al, 1998), packaging (Seth and Panigrahi, 2015), and information logistics (Dinter, 2013).…”
Section: Logistics and Distributionmentioning
confidence: 99%
“…Other researches proposed frameworks to assess the possibility of postponement in logistics, evaluating the opportunities on stocking (Pagh & Cooper, 1998), benefits of an alignment with production postponement (Rabinovich & Evers, 2003) and the implications www.intechopen.com on the whole supply chain (Yang & Burns, 2003). An extended review of postponement in logistics can be found in Yang et al (2004), to identify challenges of implementation, and in Boone et al (2007), to notice the slow rate of diffusion of this strategy.…”
Section: Literature Review and Objectives Of The Chaptermentioning
confidence: 99%
“…There is no such thing as either a universal supply chain strategy or an industry-wide supply chain (Hines, 2004). There are many types of supply chains (Hughes, Ralf & Michels, 1998;Baily, Farmer, Crocker, Jessop & Jones, 2009) and supply chain strategies are as varied as the disciplines from which they originate (Boone, Craighead & Hanna, 2007). Supply chains must be designed for strategic advantage (Ayers, 2004).…”
Section: Different Supply Chain Strategiesmentioning
confidence: 99%
“…Postponement refers to a concept whereby activities in the supply chain are delayed until a demand is realised (Boone et al, 2007). This involves intentionally delaying the execution of a task, instead of starting it with incomplete or unreliable information inputs (Yeung, Selen, Deming & Min, 2007).…”
Section: The Decoupling Pointmentioning
confidence: 99%